Produção audiovisual e redes sociais: uma experiência extensionista de difusão do acervo da Cúria Metropolitana de Belém - BARROS, Keila Siqueira de (2023)
This research aims to present an extensionist experience of transmission in Online Social Network Services (SRSO) through audiovisual production from the ecclesiastical collection of the Metropolitan Curia of Belém. To this end, bibliographical research on dissemination in archives, social networks, technologies, user studies and cultural heritage was used as methodological instruments, in addition to the survey of information collected during the execution of the extension project “Disseminating Archives: Revealing Memories and Narrating Stories”. A brief history of the project and the institutions involved is presented, as well as the procedures adopted in the planning, elaboration, and dissemination of a specific audiovisual product: the archive of the Metropolitan Curia of Belém. It is concluded that the main information about the institution and its collection were transformed into dynamic, interactive, and succinct content, facilitating its transmission to society and, therefore, promoting its access to an audience beyond the academic environment. Keywords: Diffusion in Archive; Social Networks; A